Analysis of the Current Agricultural Production System, Environmental, and Health Indicators: Necessary the Rediscovering of the Pre-hispanic Mesoamerican Diet? - Castillo, Ana María; Alavez, Valeria; Castro-Porras, Lilia; Martínez, Yuriana; Cerritos, René (Frontiers in Sustainable Food Systems, 2020)
The pre-Columbian Mesoamerican diet was characterized by being diverse, nutritionally balanced, and for integrating a remarkable diversity of plants and hundreds of animal species, mainly insects, fish, amphibians, and reptiles. In recent years, countries that used to have traditional healthy diets (e.g. Mexico, China, and India), now present some of the highest rates of diabetes, obesity, and overweight. The rise of non-communicable diseases (NCD) has been linked to the global consumption of highly processed foods, refined sugars, fats, and flours, typical to the Western diet. Additionally, the environmental footprint of the latter is high, as it requires large agricultural areas, great quantities of pesticides, and produces large amounts of greenhouse gases. Here, we show that by diversifying our current eating habits through the consumption of products that once were part of traditional diets, we could lower the prevalence of NCD, reduce greenhouse gas emissions, promote crop diversification, reduce extinction risk of species due to human activities, and at the same time, reincorporate traditions into socioeconomic processes. To this end, we reviewed World Health Organization (WHO), Food and Agriculture Organization (FAO), and World Bank databases and assessed information on health, agricultural, and environmental variables for the countries with the highest incidence of NCD, over the last 40 years. Furthermore, we focused on Mexico because it is home to the pre-Hispanic Mesoamerican world, but currently displays the highest mortality rates due to diabetes, obesity, and overweight. This country also presents an important rate of land-use change, among other negative environmental issues resulting from the adoption of the Western diet. All these factors place Mexico as an interesting case study. Finally, to mitigate the main health, environmental, and agricultural problems, we suggest that public policies around the world should strive to promote the inclusion of native products from local ancestral diets into daily meals.